How to reduce false positive results when undertaking in vitro genotoxicity testing and thus avoid unnecessary follow-up animal tests: Report of an ECVAM Workshop - Kirkland, David; Pfuhler, Stefan; Tweats, David; Aardema, Marilyn; Corvi, Raffaella; Darroudi, Firouz; Elhajouji, Azeddine; Glatt, Hansruedi; Hastwell, Paul; Hayashi, Makoto; Kasper, Peter; Kirchner, Stephan; et al. (Mutation research, 2007)
Workshop participants agreed that genotoxicity tests in mammalian cells in vitro produce a remarkably high and unacceptable occurrence of irrelevant positive results (e.g. when compared with rodent carcinogenicity). As reported in several recent reviews, the rate of irrelevant positives (i.e. low specificity) for some studies using in vitro methods (when compared to this “gold standard”) means that an increased number of test articles are subjected to additional in vivo genotoxicity testing, in many cases before, e.g. the efficacy (in the case of pharmaceuticals) of the compound has been evaluated. If in vitro tests were more predictive for in vivo genotoxicity and carcinogenicity (i.e. fewer false positives) then there would be a significant reduction in the number of animals used. Beyond animal (or human) carcinogenicity as the “gold standard”, it is acknowledged that genotoxicity tests provide much information about cellular behaviour, cell division processes and cellular fate to a (geno)toxic insult. Since the disease impact of these effects is seldom known, and a verification of relevant toxicity is normally also the subject of (sub)chronic animal studies, the prediction of in vivo relevant results from in vitro genotoxicity tests is also important for aspects that may not have a direct impact on carcinogenesis as the ultimate endpoint of concern. In order to address the high rate of in vitro false positive results, a 2-day workshop was held at the European Centre for the Validation of Alternative Methods (ECVAM), Ispra, Italy in April 2006. More than 20 genotoxicity experts from academia, government and industry were invited to review data from the currently available cell systems, to discuss whether there exist cells and test systems that have a reduced tendency to false positive results, to review potential modifications to existing protocols and cell systems that might result in improved specificity, and to review the performance of some new test systems that show promise of improved specificity without sacrificing sensitivity. It was concluded that better guidance on the likely mechanisms resulting in positive results that are not biologically relevant for human health, and how to obtain evidence for those mechanisms, is needed both for practitioners and regulatory reviewers. Participants discussed the fact that cell lines commonly used for genotoxicity testing have a number of deficiencies that may contribute to the high false positive rate. These include, amongst others, lack of normal metabolism leading to reliance on exogenous metabolic activation systems (e.g. Aroclor-induced rat S9), impaired p53 function and altered DNA repair capability. The high concentrations of test chemicals (i.e. 10 mM or 5000 μg/ml, unless precluded by solubility or excessive toxicity) and the high levels of cytotoxicity currently required in mammalian cell genotoxicity tests were discussed as further potential sources of false positive results. Even if the goal is to detect carcinogens with short in vitro tests under more or less acute conditions, it does not seem logical to exceed the capabilities of cellular metabolic turnover, activation and defence processes. The concept of “promiscuous activation” was discussed. For numerous mutagens, the decisive in vivo enzymes are missing in vitro. However, if the substrate concentration is increased sufficiently, some other enzymes (that are unimportant in vivo) may take over the activation—leading to the same or a different active metabolite. Since we often do not use the right enzyme systems for positive controls in vitro, we have to rely on their promiscuous activation, i.e. to use excessive concentrations to get an empirical correlation between genotoxicity and carcinogenicity. A thorough review of published and industry data is urgently needed to determine whether the currently required limit concentration of 10 mM or 5000 μg/ml, and high levels of cytotoxicity, are necessary for the detection of in vivo genotoxins and DNA-reactive, mutagenic carcinogens. In addition, various measures of cytotoxicity are currently allowable under OECD test guidelines, but there are few comparative data on whether different measures would result in different maximum concentrations for testing. A detailed comparison of cytotoxicity assessment strategies is needed. An assessment of whether test endpoints can be selected that are not intrinsically associated with cytotoxicity, and therefore are less susceptible to artefacts produced by cytotoxicity, should also be undertaken. There was agreement amongst the workshop participants that cell systems which are p53 and DNA-repair proficient, and have defined Phase 1 and Phase 2 metabolism, covering a broad set of enzyme forms, and used within the context of appropriately set limits of concentration and cytotoxicity, offer the best hope for reduced false positives. Whilst there is some evidence that human lymphocytes are less susceptible to false positives than the current rodent cell lines, other cell systems based on HepG2, TK6 and MCL-5 cells, as well as 3D skin models based on primary human keratinocytes also show some promise. Other human cell lines such as HepaRG, and human stem cells (the target for carcinogenicity) have not been used for genotoxicity investigations and should be considered for evaluation. Genetic engineering is also a valuable tool to incorporate missing enzyme systems into target cells. A collaborative research programme is needed to identify, further develop and evaluate new cell systems with appropriate sensitivity but improved specificity. In order to review current data for selection of appropriate top concentrations, measures and levels of cytotoxicity, metabolism, and to be able to improve existing or validate new assay systems, the participants called for the establishment of an expert group to identify the in vivo genotoxins and DNA-reactive, mutagenic carcinogens that we expect our in vitro genotoxicity assays to detect as well as the non-genotoxins and non-carcinogens we expect them not to detect.